Credit Ratings and Security Prices in the Subprime MBS Market - Ashcraft, Adam; Goldsmith-Pinkham, Paul; Hull, Peter; Vickery, James (American Economic Review, 2011)
We present and discuss preliminary evidence suggesting that credit ratings significantly influenced prices for subprime mortgage-backed securities issued in the period leading up to the recent financial crisis. Ratings are closely correlated with prices even controlling for a rich set of security- and loan-level controls. This incremental variation in ratings has much less predictive power for security defaults, however, based on findings to date from our ongoing research, suggesting prices were excessively sensitive to ratings relative to their informational content.